Translating Figurative Language in the Quran: An Analytical Study - Alasbli, Najla Abdulrahman (Journal of Humanities & Social Sciences, 2020)
Translating the Holy Qur’an poses a serious challenge for translators for different reasons; the most important of these is that any mistake or distortion, whether intentional or unintentional, cannot be overlooked or tolerated. Mistakes such as translation loss, semantic inaccuracy, absence of an accurate equivalent, etc are all to be expected in rendering a linguistically-rich and figuratively-loaded book like the Holy Qur’an. Therefore, rendering the figurative language is one of the challenging problems that lie at the heart of translation. This paper will carefully explore and review the difficulties encountered by translators in rendering examples of figurative language in the Chapter of Taha, with the aim of providing suggestions that will assist in decreasing translation loss. It will also present an analysis of the choices made by some translators and how each of them tries to keep the effect of figurative language and reduce the amount of loss. This paper will put effort to plumb the depths of reviewing the difficulties faced by translators rendering figurative language in one Chapter of the Qur’an, and raises the question of whether or not the translation choices opted for by two selected translators reflect and achieve the level of the acceptability in expressing the intended meaning of figurative language. This paper may open up new horizons for translators in their future studies, and for researchers to follow suit and a fulcrum on which future researchers could depend.